Parents Strategies in Stimulating Early Children’s Language Development through Handphone (Phenomenological Study in Girimoyo Village) - Retno, Ambarukmi Harko Anjali; Wahyuni, Sri; Choiro, Umu Da'watul (Universitas Negeri Malang, 2024)
This research is based on the fact that in 2022, almost half of young children will use cell phones. This happened because all education groups, including the early age group, carried out teaching and learning activities from home via cellphone during the COVID-19 pandemic. Parents act as guides for their children and provide technology in the form of mobile phones to adapt to the needs and developments of the times. In early childhood, language development is an important developmental stage in a child's golden years. We need to encourage this language development so that children can develop according to their age. The aim of this research is to describe the strategies used and the obstacles parents face when encouraging children's language development via cell phones. This research uses a qualitative approach. This research uses observation, interviews and written methods to collect data. The data obtained was analyzed in the following stages: 1) data collection, 2) data reduction, 3) data interpretation, 4) graphic design. Source and method triangulation was used to check the accuracy of the data. The results of this research show that the strategies used by parents are parents choosing the right applications/content, setting time limits for using cellphones, controlling and supervising handphone use, ensuring cellphones do not interfere with interactions with and balancing handphone use with interactions. The obstacles they face include dependency, the appearance of inappropriate content, time constraints, and emotional problems (mood) that change easily.